Allantoate amidohydrolase transcript expression is independent of drought tolerance in soybean - Charlson, Dirk V. (Oxford University Press, 2009)
Drought is a limiting factor for N(2) fixation in soybean [Glycine max (L.) Merr.] thereby resulting in reduced biomass accumulation and yield. Drought-sensitive genotypes accumulate ureides, a product of N(2) fixation, during drought stress; however, drought-tolerant genotypes have lower shoot ureide concentrations, which appear to alleviate drought stress on N(2) fixation. A key enzyme involved in ureide breakdown in shoots is allantoate amidohydrolase (AAH). It is hypothesized that AAH gene expression in soybean determines shoot ureide concentrations during water-deficit stress and is responsible for the differential sensitivities of the N(2)-fixation response to drought among soybean genotypes. The objectives were to examine the relationship between AAH transcript levels and shoot ureide concentration and drought tolerance. Drought-tolerant (Jackson) and drought-sensitive (Williams) genotypes were subjected to three water-availability treatments: well-watered control, moderate water-deficit stress, and severe water-deficit stress. Shoot ureide concentrations were examined, in addition to gene expression of AAH and DREB2, a gene expressed during water-deficit stress. As expected, DREB2 expression was detected only during severe water-deficit stress, and shoot ureide concentrations were greatest in the drought-sensitive genotype relative to the drought-tolerant genotype during water-deficit stress. However, expression of AAH transcripts was similar among water treatments and genotypes, indicating that AAH mRNA was not closely associated with drought tolerance. Ureide concentrations in shoots were weakly associated with AAH mRNA levels. These results indicate that AAH expression is probably not associated with the increased ureide catabolism observed in drought-tolerant genotypes, such as Jackson. Further study of AAH at the post-translational and enzymatic levels is warranted in order to dissect the potential role of this gene in drought tolerance.